The Role of Ionic Liquids in Performance Enhancement of Two‐Step Perovskite Photovoltaics. Issue 1 (8th November 2022) - Liang, Xiao; Duan, Dawei; Al-Handawi, Marieh B.; Wang, Fei; Zhou, Xianfang; Ge, Chuang-ye; Lin, Haoran; Zhu, Quanyao; Li, Liang; Naumov, Panče; Hu, Hanlin
Abstract : Much of the research efforts of late that are directed toward enhancement of the efficiency of perovskite‐based photovoltaics are focused on the application of ionic liquids (ILs) in a one‐step approach. On the contrary, the details of the alternative two‐step approach, such as the role of the ILs in the perovskite film solidification and its optoelectronic properties, remain poorly understood despite the increasing evidence that this latter method might offer considerable advantages, including better reproducibility and control over crystallization. Herein, the effect of IL methylammonium acetate (MAAc) introduced into the PbI2 layer by a sequential deposition process on the optoelectronic properties of the perovskite film and the performance of the ensuing photovoltaic devices are studied. The addition of MAAc lowers the MAAc–perovskite formation enthalpy, leading to an accelerated solidification process. Moreover, MAAc suppresses the formation of Pb 0, thereby facilitating the perovskite formation while lowering the deep defect states caused by Pb 0 . In addition to grain boundary passivation, the acetate ions can diffuse into the bulk of the perovskite material, filling up the halide vacancies with reduced trap state density. As a result, a decent power conversion efficiency of 23.36% is achieved, with noticeably improved durability. Abstract : Ionic liquid methylammonium acetate (MAAc) is introduced into the PbI2 layer to produce a perovskite film via a two‐step method. Systematic investigations on the influence of MAAc on the perovskite formation mechanism are performed. The theoretical calculations confirm that Ac − can occupy the iodine vacancy of the perovskite material in the bulk and on the surface. The final device shows improvement of the power conversion efficiency over 23%.